Competitiveness of Regulatory Justice at Palestinian Universities when Practicing Information Security Standard (ISO/IEC 27002) in Light of Regulatory Symmetry: A Strategic Developmental Practical Proposal - Nidal Hamdan Mustafa Al-Masri; Mhammed Ahmed Oda El.agha (University of Science and Technology, Yemen, 2018)
The research aimed to propose a framework for achieving competition between Palestinian universities through their  practice of Information Security Standard (ISO/IEC 27002) in order to influence regulatory justice and regulatory symmetry, using the descriptive analytical method. To achieve the research objectives, the researchers used a questionnaire as a tool to collect information and administered it to a sample consisting of 214 employees from senior and middle management at Palestinian universities in Gaza Strip. The research revealed the following major results: The mean of all items of the practice of (ISO / IEC 27002) was %84.37; the mean of  all items referring to the availability of competitiveness was % 85.74; the mean of all items referring to  regulatory justice was %76.98; and the mean of all items referring to regulatory symmetry was %88.41. The results also showed a positive relationship between these dimensions: the practice of ISO / IEC 27002 and the achievement of competition and regulatory justice; the availability of regulatory justice and the achievement of regulatory symmetry; and regulatory justice and competitiveness. However, there was no relationship between these dimensions: the practice of ISO / IEC 27002 and the achievement of regulatory symmetry; regulatory symmetry and competitiveness. Keywords: Regulatory justice, Regulatory symmetry, Competitiveness, Information security.